Joint Source-Channel Coding for Wireless Image Transmission based OFDM-IDMA Systems - A. Salman, Salah.; A. Rajab, Maha. (Iraqi Journal of Science, 2023)
The source and channel coding for wireless data transmission can reducedistortion, complexity and delay in multimedia services. In this paper, a joint sourcechannelcoding is proposed for orthogonal frequency division multiplexing -interleave division multiple access (OFDM-IDMA) systems to transmit thecompressed images over noisy channels. OFDM-IDMA combines advantages ofboth OFDM and IDMA, where OFDM removes inter symbol interference (ISI)problems and IDMA removes multiple access interference (MAI). Convolutionalcoding is used as a channel coding, while the hybrid compression method is used asa source coding scheme. The hybrid compression scheme is based on wavelettransform, bit plane slicing, polynomial approximation model and absolute momentblock truncation. The wavelet transform is exploited to decompose the image intoapproximation and detail sub bands, while the polynomial model is used to code theapproximation image band. Simulation results show that the proposed systemreduces distortion efficiently (i.e., preserving image quality) and achieves a simplemethod for image multiuser transmission over wireless channels.